(untitled) (Euro-Asia Conferences, 2021)
The idea of quality and quality management of education is one of the most relevant at the present stage of development for the Uzbek school. Improving the quality of education in secondary schools is, first of all, the correct formation of the teaching staff of the school, the definition of specific goals and objectives for the teaching staff and monitoring their implementation. The positive component of this approach is that during its implementation, both the continuity of the Uzbek traditions of education is preserved, and the set of positions that best meet the modern needs of society and standards is expanded. The quality of education is understood as its compliance with the existing requirements, norms and standards, the needs of society and production. In the course of the study, a complex of theoretical and empirical methods was used: analysis of scientific literature, generalization, systematization, modeling, observation, study of pedagogical experience, pedagogical expertise.